2011
DOI: 10.1055/s-0031-1279725
|View full text |Cite
|
Sign up to set email alerts
|

Acute Encephalopathy in a Patient with Dravet Syndrome

Abstract: Dravet syndrome (severe myoclonic epilepsy in infancy) is an epileptic syndrome with various types of seizures that begin in the first year of life and may result in intellectual impairment. Mutations of the SCN1A gene are the most prevalent genetic cause of Dravet syndrome. In this study, we report a 12-year-old girl with Dravet syndrome carrying an SCN1A mutation, c.2785Cdel (L929del fsX934). She had an episode of status epilepticus and persistent lethargy after 48 h of acute febrile illness that was precede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…McIntosh et al reported that 45% of DS patients who presented a first seizure in proximity of vaccination might experience a SE [21]. Tsuij et al described a patient with DS with a SE associated with AE after influenza vaccination; fortunately, without a fatal outcome [22]. Recently, Deng et al reported a fatal SE following vaccination in a 12 month-old boy with SCN1A genetic variant [23]; clinical phenotype of this patient was suggestive of 'generalized epilepsy with febrile seizures plus' (GEFS+) rather than DS.…”
Section: Discussionmentioning
confidence: 99%
“…McIntosh et al reported that 45% of DS patients who presented a first seizure in proximity of vaccination might experience a SE [21]. Tsuij et al described a patient with DS with a SE associated with AE after influenza vaccination; fortunately, without a fatal outcome [22]. Recently, Deng et al reported a fatal SE following vaccination in a 12 month-old boy with SCN1A genetic variant [23]; clinical phenotype of this patient was suggestive of 'generalized epilepsy with febrile seizures plus' (GEFS+) rather than DS.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that although the condition worsens progressively compared to healthy children there is no loss of abilities since all patients acquired new skills during follow-up. Obviously, this does not apply to the rare patients who had developed major anoxic-ischemic sequelae after severe and complicated status epilepticus with atrophy of supratentorial structures [23] or lesions in the subcortical structures [24] and who were therefore not included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These 15 patients were a subject of this study. The clinical course of patient 11 was presented elsewhere as a case report (Tsuji et al., 2011). The approximate number of the patients with Dravet syndrome who were regularly followed was available from 12 hospitals.…”
Section: Methodsmentioning
confidence: 99%